Examining Pre-Service Teachers’ Perceptions About Virtual Classrooms in Online Learning - Debbag, Murat; Fidan, Mustafa (International Review of Research in Open and Distributed Learning, 2022)
Using a descriptive research design, this study explored pre-service teachers’ perceptions of synchronous virtual classrooms and Web camera use in online learning. The study sample consisted of 256 pre-service teachers from the education faculty of a university in Turkey, and data was collected using a survey. The results showed that most pre-service teachers did not want to open their own Web cameras, due to reasons such as unsuitable physical environment, unsuitable appearance, and distractions on the screen. In addition, they stated that instructors’ gestures, facial expressions, and verbal-visual emphases were essential, and they wanted instructors to be visible on screen. They also suggested that student-centered practices and question-answer activities should be carried out to increase the effectiveness of virtual classrooms. In addition, sessions should not be scheduled in the early hours of the day, and should be of short duration.